PERANAN PENGASUH ANAK (BABY SITTER) DALAM PEMBENTUKAN SIFAT DAN SIKAP ANAK (Studi di Perumahan Bukit Bakung Indah Bandar Lampung) - Utami, Rezza Evana Rossi; Milyan, Paraswati Daril (SOCIOLOGIE, 2013)
Research problem is how the caregiver role in shaping the nature and attitude of the child, considering the role of mother urban communities largely supplanted by other institutions. Research objective is to determine the role of caregivers in shaping the nature and attitude of the child. This type of research uses qualitative research using primary data types obtained from in-depth interviews with informants. Informants in this study amounted to 6 people consisting of 2 people nannies, two mothers working women and housewives 2 people. Data analysis techniques using data reduction, data presentation, and conclusion. These results indicate the background of urban society where every family is working couples. As a result, the role of the mother who should provide care and treatment to children optimally replaced by others ie nanny. Caregivers who plays surrogate mother to establish the nature and attitude of his foster children because of the intensity of the child more time with caregivers. Children will be more interaction and communication with caregivers. Time together will create dependency relationship and the child will be closer to the nanny than with her birth mother. However, the use of caregivers are impact will be generated both positive and negative impacts.Keywords: Caregivers, role, attitudes of children